Pengaruh Tingkat Pendidikan Dan Usia Karyawan Terhadap Produktivitas Kerja (Studi Kasus Perkebunan Semangka dan Melon Karang Barat Banyusokah Ketapang Sampang) - Noruddin Noruddin; Budi Wahono; Ita Athia (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstrackThis study aims to determine the effect of education level and employee age on work productivity of employees of plantation melon and watermelon Karang Barat. The sample used in this study were 50 production employees. The data analysis method used in this research is quantitative data analysis using multiple linear regression analysis. The data testing used is simultaneous hypothesis testing (F) and partial hypothesis testing (t). The results showed that simultaneously the variables education level and age have a significant effect on work productivity variables. Based on the partial test results, the variables education level and age variables have a significant effect on work productivity variables of plantation melon and watermelon Karang Barat. Keywords: Education Level, Age and Work Productivity.